2004
DOI: 10.1007/s00240-003-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dehydroepiandrosterone on renal ischemia-reperfusion-induced oxidative stress in rabbits

Abstract: Reactive oxygen species (ROS) can play an important role in the pathogenesis of ischemia-reperfusion (I/R) injury. Dehydroepiandrosterone (DHEA) is one of the hormones secreted from adrenal glands, and in some studies it has been shown that DHEA has antioxidant properties. This experimental study was designed to determine the effect of DHEA on I/R-induced oxidative stress in rabbit kidney. Twenty-one rabbits were divided into three groups. Rabbits were subjected to 60 min of left renal pedicle occlusion follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
1
17
0
2
Order By: Relevance
“…Other possible beneficial actions of DHEAS in animal models of diabetes may include elevation of glucose transporter expression by preventing cortisol-induced transporter down-regulation as well as preventing cortisol's anti-insulin and gluconeogenesic actions. In addition, the antioxidant capacity of DHEAS may suppress inflammatory damage to pancreatic b-cells in vivo, mimicking, to some extent the anti-inflammatory action of glucocorticoids (Aksoy et al 2004;Iwasaki et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Other possible beneficial actions of DHEAS in animal models of diabetes may include elevation of glucose transporter expression by preventing cortisol-induced transporter down-regulation as well as preventing cortisol's anti-insulin and gluconeogenesic actions. In addition, the antioxidant capacity of DHEAS may suppress inflammatory damage to pancreatic b-cells in vivo, mimicking, to some extent the anti-inflammatory action of glucocorticoids (Aksoy et al 2004;Iwasaki et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…ROS have been implicated in the pathogenesis of renal injury after I/R. 7 Free radical formation is discussed as an important mechanism of renal injury induced by SWL. 1,15,17,18 In the study of Bomanji et al 6 it was shown that SWL causes a transient decrease in renal perfusion that returns to the normal range within a definite time period and ROS are produced during this period.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that oxygenfree radicals play a vital role in the development of renal parenchymal damage during ischemia-reperfusion (I/R) period. 7 Excess production of free radicals during ischemia or impaired antioxidant mechanisms may cause oxidative stress. Oxidative stress may induce a number of pathophysiological processes and result in cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of DHEA has been shown in various forms of T/D injury, including kidney [8], muscle flap [9], and brain [10]. However, no study has investigated the role of DHEA in testicular T/D injury.…”
Section: Index Wordsmentioning
confidence: 97%